2014
DOI: 10.17221/91/2014-pse
|View full text |Cite
|
Sign up to set email alerts
|

Yield and grain quality of spring barley as affected by biomass formation at early growth stages

Abstract: Timely and reliable prediction of grain yield and quality of spring barley represents a key prerequisite for effective crop management. Within this study we evaluated the relationships between yield components, grain quality, biomass production and the number of tillers in different growth stages. For this purpose, in three years (2011)(2012)(2013) multifactorial field trials focused on the combined effects of cultivar, sowing density and nitrogen nutrition were conducted. Based on ANOVA it was found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 11 publications
(7 reference statements)
5
23
0
1
Order By: Relevance
“…Similar results were found by Křen et al (2014), who analysed spring barley yields applying different N fertilisation rates. The yield increase was determined to be higher using N rate from 0 kg N/ha to 45 kg N/ha, rather than the rate from 45 kg N/ha to 90 kg N/ha.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were found by Křen et al (2014), who analysed spring barley yields applying different N fertilisation rates. The yield increase was determined to be higher using N rate from 0 kg N/ha to 45 kg N/ha, rather than the rate from 45 kg N/ha to 90 kg N/ha.…”
Section: Discussionsupporting
confidence: 86%
“…Positive relationship between NDVI values at anthesis and grain yield was probably the result of high association between NDVI values and crop biomass, as previously reported in different studies (Aparicio et al, 2000;Moges et al, 2005). Moreover, grain yield in tworowed barley is the result of establishing high number of spikes per unit area (Mirosavljevic et al, 2018), and increase in crop biomass is associated with improvement of spike number (Křen et al, 2014). Also, Prado et al (2017) reported that high biomass was positively related with grain yield in wheat and barley.…”
Section: Relationship Among Studied Traitssupporting
confidence: 60%
“…These results suggest that the growth regulators, particularly azoxystrobin and trinexapac-ethyl, were able to partially eliminate the adverse effect of the year 2014, which was characterized by lower formation of productive tillers. Relatively dry weather and high temperatures during tillering in 2014 (Table 1) were probably the cause of accelerated plant development and reduced number of strong tillers able to form productive stems (Křen et al 2014). Similarly to grain yield the inter-annual differences in spike productivity were mostly reduced by the application of azoxystrobin.…”
Section: Resultsmentioning
confidence: 99%